Minimally invasive plate osteosynthesis with locking compression plate for proximal and distal diametaphyseal tibial fracture - Thapa, Upendra Jung; Sapkota, Krishna; Wahegaonkar, Krishna; Ranjeet, Niraj; Thapa, Pabin; Onta, Pratyenta Raj (Asian Journal of Medical Sciences, 2018)
Background: The treatment of proximal and distal diametaphysealtibial fractures remains controversial. This study was performed to evaluate the results of Locking compression plate using MIPO technique in the management of proximal and distal diametaphysealtibial fracture. Aims and Objective: To analyse and observe the result of management of metaphyseal fractures of tibia with respect to operative technique, stability of fixation, union of fracture, post-operative range of motion and complication. Materials and Methods: The study was prospective study. Forty two patients who sustained fractures of proximal and distal dia-metaphyseal tibial fractures with or without articular involvement were included in the study and treated by employing the concept of Minimally invasive plate osteosynthesis during period of August 2015 to December 2017 and followed up at regular interval with minimum six months to thirty months. Intervention: Surgical reduction and fixation of fracture using proximal and distal anatomical locking compression plate followed by rehabilitation. Main outcome measure: Radiological outcome, perioperative and postoperative complication, postoperative alignment, range of motion. Results: All fractures got united with the average duration of 22.7 weeks for proximal metadiaphyseal tibia and 19.9 weeks for distal diametaphysealtibia. There were 3 delayed union cases which got united without any surgical intervention. Deep peroneal nerve palsy was seen in 2 cases with proximal tibia fracture treated with longer plate. 2 cases of superficial infection and one deep infection seen with proximal diametaphyseal fracture and 2 superficial infection with one case of wound dehiscence and implant prominent seen with distal diametaphyseal tibia fracture. No malalignment or angulation of more than 10 degree occurred in any plane for both proximal and distal diametaphyseal fractures. Conclusion: MIPO provides stable fixation with excellent union rate with minimal complication for both proximal and distal diametadiaphysealtibial fracture. Asian Journal of Medical Sciences Vol.9(6) 2018 76-83